Hierarchical resource deployment and sharing strategy in mobile edge computing - Houhao ZHANG; Hanlin LI; Lin GAO (物联网学报)
With the coming of 5G, Internet of things (IoT) has gradually become a reality.However, the function of many terminals is limited to insufficient computing resources in IoT.Mobile edge computing (MEC) is a new network paradigm, where terminals can offload the resource sensitive applications to nearby edge services with rich resources, and thus reduced the operational cost/delay and increased the quality of service (QoS).The resource deployment of MEC was studied, a scenario was considered that the Internet service provider (ISP) paid for deploying the MEC resources, and meanwhile gained revenue from leasing resources to terminals.Note that the deployment of MEC resource is a long-term strategy, while the demands from terminals are time varying.Therefore, it is critical to deploy the MEC resource properly.A hierarchical architecture built upon the 5G radio access network for MEC resource deployment and sharing was proposed, where the MEC resource could be deployed at different network levels.Based on the hierarchical network architecture, the optimal MEC resource deployment problem was formulated and solved as a mixed integer programming problem, aiming at maximizing the ISP’s revenue.And the CVX toolbox in MATLAB was used to solve the problem.Simulation results demonstrate that the proposed solution outperforms the flat resource deployment solution in terms of both the ISP’s revenue and the deployment cost.